BACULOVIRUS BIOPESTICIDES: AN OVERVIEW - A. Beas-Catena; A. Sánchez Mirón; F. García-Camacho; A. Contreras-Gómez; E. Molina-Grima (Journal of Animal and Plant Sciences, 2014)
Baculoviruses have shown to be a good tool for insect pest control. Numerous natural baculoviruses have been used as biopesticides worldwide as they are naturally occurring pathogens, highly specific with limited host range, and without lethal effects on non-target organisms. Slow speed of kill of wild-type baculoviruses when compared to chemical insecticides is a serious disadvantage that has promoted the development of large number of recombinant baculoviruses, mainly with genes encoding insect-specific toxins from scorpions or spiders, which kill insects faster than the parent wild-type virus. However, uptill today no recombinant baculovirus-based pesticides are commercially available. For the expansion of baculovirus pesticides some drawbacks have to be overcome. Current methods for large scale in vitro production have to be improved in order to circumvent their technical limitations, and developments of new and more effective additives to improve the stability of baculoviruses in pesticide formulation are needed. Nonetheless, recombinant baculoviruses are expected to strongly contribute to the expansion of baculovirus pesticides use in the next future, as the negative social perception of genetically modified organisms, including genetically modified baculoviruses, decreases.
Keywords: Baculovirus; biopesticide; recombinant; production; formulation